THE EFFECT OF ASSET STRUCTURE, LIQUIDITY, AND TAX AVOIDANCE ON CAPITAL STRUCTURE WITH PROFITABILITY AS A MODERATING VARIABLE (A STUDY OF ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) 2019-2022) - Muhammad Zahrul Fuadi; Jummaini; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This research was conducted to see the influence of Asset Structure, Liquidity, Tax Avoidance, and Profitability Moderation variables on Capital Structure in Energy Sector Companies listed on the Indonesia Stock Exchange (BEI). The sampling technique in this research was purposive sampling. The sample used in this research was all companies in the energy sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period, totaling 81 companies. The data collection method used is documentation. Documentation is the aim of obtaining data directly from the research site, including relevant books, regulations, activity reports and data relevant to the research. The variables in this research include the dependent variable, namely Capital Structure (DER), and the independent variables in this research are Asset Structure (SA), Liquidity (CR), Tax Avodance (TA) and Profitability (ROA). The results that can be concluded are that Asset Structure has a significant effect on the Capital Structure of energy sector Companies listed on the Indonesia Stock Exchange (BEI), Liquidity, Tax Avoidance and profitability do not have a significant effect on the Capital Structure of energy sector Companies listed on the Indonesia Stock Exchange (BEI ), Profitability does not moderate the relationship between Asset Structure, Liquidity and Tax Avoidance on Capital Structure in energy sector companies listed on the Indonesia Stock Exchange (BEI).